2019
DOI: 10.1371/journal.pone.0225952
|View full text |Cite
|
Sign up to set email alerts
|

The spatio-temporal patterns of the topsoil organic carbon density and its influencing factors based on different estimation models in the grassland of Qinghai-Tibet Plateau

Abstract: The grassland soils of the Qinghai-Tibet Plateau (QTP) store a large amount of organic carbon because of the cold, humid climate, and topsoil organic carbon is quite sensitive to global climate changes. However, the spatio-temporal dynamics and factors that influence the soil organic carbon (SOC) on the QTP’s grassland are not understood well. Moreover, there are few comparative analyses of different approaches to estimate the QTP’ SOC. In this study, we estimated the storage and patterns of SOC density (SOCD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The study's findings demonstrated that the SOC in grassland ecosystem was mostly influenced by MAT and BD. These findings are in agreement with past regional and national studies of grasslands conducted in China, including those conducted in the Hexi Corridor (Wang et al, 2014) and the Qinghai-Tibet Plateau (Liu et al, 2019), and found that soil TN, MAP, soil type, MAT provided the most reliable predictors of total SOC density in Chinese shrublands. The results were generally consistent with ours (Figure 3).…”
Section: Drivers Of Socsupporting
confidence: 91%
“…The study's findings demonstrated that the SOC in grassland ecosystem was mostly influenced by MAT and BD. These findings are in agreement with past regional and national studies of grasslands conducted in China, including those conducted in the Hexi Corridor (Wang et al, 2014) and the Qinghai-Tibet Plateau (Liu et al, 2019), and found that soil TN, MAP, soil type, MAT provided the most reliable predictors of total SOC density in Chinese shrublands. The results were generally consistent with ours (Figure 3).…”
Section: Drivers Of Socsupporting
confidence: 91%
“…Meanwhile, a significant portion of it is underlaid by permafrost, and with climate warming, permafrost thawing is likely to occur. These changes have induced changes in the ecosystem carbon processes, such as carbon gains attributed to stimulated vegetation productivity and carbon losses from thawing permafrost; the balance of these fluxes depends on the feedback of permafrost to warming [30,61]. In fact, the increase in carbon inputs from vegetation caused by climate change was greater than the loss of carbon, resulting in an obvious increase in ecosystem carbon storage during the study period.…”
Section: Temporal Dynamics and Factors Influencing Ecosystem Carbon S...mentioning
confidence: 99%
“…Reviewing previous studies, we found that four main methods are used to estimate carbon density: literature reviews, field measurements, empirical modeling, and remote sensing. Due to differences in the estimation methods, the results may vary greatly [30]. Some studies used MODIS-NDVI products to establish the relationship between biomass and SOCD and demonstrated the scientific adaptability of this approach [30,[49][50][51].…”
Section: Parameter Inversion Of the Key Carbon Poolmentioning
confidence: 99%
See 2 more Smart Citations